A survey of trauma alert criteria and handover practice in England and Wales. Issue 4 (23rd March 2007) - Budd, Henry Robert; Almond, Lawrence Maximilian; Porter, Keith
Abstract : Introduction: Appropriate alerting of patients with trauma and informative handover are necessary to allow a smooth transition of care between the prehospital and hospital teams. Aim: To identify current practice and areas that need to be improved to facilitate the transition from prehospital care to emergency department resuscitation. Methods: A questionnaire postal study of 100 emergency departments and all 32 ambulance service trusts in England and Wales. Results: Emergency departments returned 34 (34%) completed questionnaires, and ambulance trusts returned 16 (50%) completed questionnaires. In all, 56.8% of emergency department responders stated that trauma alert information was relayed through ambulance control, 48.5% stated that alert messages were standardised and 18.5% felt that ambulance crews used the trauma severity scoring system during alerting. 64.7% stated that handover was broadcast to the trauma team and 9.1% routinely received digital photographic images. All ambulance service responders included injury mechanism in their alerting criteria and 53.3% used a standard handover structure with 86.7% familiar with the mnemonic ASHICE (Age, Sex, History, Injuries, Condition, Expected time of arrival) for rapid information transmission. Discussion: Greater cooperation between regional emergency departments and ambulance services is necessary to refine the alerting and handover process, producing a pathway through which vital information is collected by trained personnel and communicated without distortion to the resuscitation room, where it may be utilised to inform life-saving decisions.